The design of pitch oscillation mechanism and measurument system of an aerofoil [electronic resource - Zulkhairi Subari @ Rahmat, 1984- (2008)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal-Aeronautik)) - Universiti Teknologi Malaysia, 2008